Presentation of the final document of the rural development and local institutionality table: Rural development as a challenge to the Church of the South Andean - Casazola Ccama, Juan (1999)
On the threshold of the next millennium, we can see that many changes have taken place, one of them being globalization. The phenomenon of globalization is linked to the forms and modalities that have taken the production and trade of goods in the world, as well as services and international finance. These changes that have occurred in recent years are the result of a set of technological innovations fundamentally linked to the notable advances made in information technology and telecommunications, in the use of bioenergy and genetic manipulation.